Negative myoclonus as a manifestation of cefepime neurotoxicity - Daichi Umemoto; Hirokazu Kuroda; Hiroaki Nishioka (Clinical Case Reports, 2024)
Key Clinical Message Negative myoclonus may present in the early stages of cefepime neurotoxicity. Cefepime neurotoxicity typically presents as reduced consciousness, myoclonus, and seizures; however, negative myoclonus is uncommon. This video shows an older woman with cefepime neurotoxicity that presented as a negative myoclonus of the upper limbs.